The Values of Islamic Education in Nasyid Songs on the Indonesian Language Edition of One4kids Youtube Channel by Subhi Alshaik - Dedy Yansyah; Irfan Anshori; Rodiatul Mutmainah; Suheri Suheri; Zaenuri Zaenuri (research, training and philanthropy institution Natural Aceh, 2023)
This study aims to discover the values ​​of Islamic education in Subhi Alshaik's One4kids nasyid song. Besides that, this study aims to inform parents that the One4kids nasyid song by Subhi Alshaik can provide a stimulus for understanding and religious guidance for children. This type of research is qualitative research, using the method of literature. The sample used in this study consisted of primary and secondary data. The primary data is the One4kids nasyid song by Subhi Alshaik. Secondary data, namely journals, books, and videos. Data collection techniques in this study through observation and documentation. The data analysis used in this research is the content analysis technique. The results of research on the values ​​of Islamic education contained in the One4kids nasyid song on three selected themes, there are values ​​Islamic education, namely First, Faith Education (aqidah), namely contemplating the signs of Allah's power and being grateful for His blessings. Second, Islamic Education (worship), which worships Allah through the teachings of the Sunnah of the Prophet Muhammad. Third, Moral Education, namely being a good person in life. This research has implications as part of parents' efforts to develop children's Islamic educational values ​​through the use of YouTube social media to follow the development of science and technology in the era of Society 5.0.